2015
DOI: 10.1186/s40635-015-0063-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of dexamethasone in scorpion venom-induced deregulation of sodium and water transport in rat lungs

Abstract: BackgroundSevere scorpion envenomation can evolve to lung injury and, in some cases, death. The lung injury could be attributed to acute left ventricular failure and increased pulmonary vascular permeability secondary to the release of inflammatory mediators. In clinical practice, corticosteroids have been administered to reduce the early side effects of the anti-venom. We propose to study the effects of Tityus serrulatus venom and dexamethasone on pulmonary expression of sodium and water transporters, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Although the mechanisms by which the immune system detects venom components and initiates inflammation, as well as the signaling pathways that regulate the immune response, remain unknown, a number of studies indicates the implication of pattern recognition receptors (PRRs) located on innate immune system cells, such as Toll-like receptors (TLRs), in these processes. While TLRs are usually activated by ligands of bacterial or viral origin (pathogen-associated molecular patterns) or by endogenous compounds (damage-associated molecular patterns), recent studies indicate that TLR2 and TLR4 can also recognize non-microbial ligands, including certain venom components (so-called venom-associated molecular patterns) with following stimulation of pro-inflammatory pathways ( Martin-Eauclaire et al, 2019 ; Malaque et al, 2015 ; Reis et al, 2019 ). For instance, it was found that T. serrulatus venom, interacting with TLR2, TLR4 and CD14 of macrophages, activates these cells and through NF-κB- and AP-1-dependent signaling pathways promote them to generate the cytokines and lipid mediators ( Ryan et al, 2021 ; Zoccal et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms by which the immune system detects venom components and initiates inflammation, as well as the signaling pathways that regulate the immune response, remain unknown, a number of studies indicates the implication of pattern recognition receptors (PRRs) located on innate immune system cells, such as Toll-like receptors (TLRs), in these processes. While TLRs are usually activated by ligands of bacterial or viral origin (pathogen-associated molecular patterns) or by endogenous compounds (damage-associated molecular patterns), recent studies indicate that TLR2 and TLR4 can also recognize non-microbial ligands, including certain venom components (so-called venom-associated molecular patterns) with following stimulation of pro-inflammatory pathways ( Martin-Eauclaire et al, 2019 ; Malaque et al, 2015 ; Reis et al, 2019 ). For instance, it was found that T. serrulatus venom, interacting with TLR2, TLR4 and CD14 of macrophages, activates these cells and through NF-κB- and AP-1-dependent signaling pathways promote them to generate the cytokines and lipid mediators ( Ryan et al, 2021 ; Zoccal et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies demonstrate that dexamethasone doesn't have any benefits in the management of scorpion sting (Bahloul et al, 2013;Malaque et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the results of other studies, corticosteroids have not shown any benefit in the management of scorpion stings. [42][43][44]…”
Section: Discussionmentioning
confidence: 99%